2012
DOI: 10.3174/ajnr.a2967
|View full text |Cite
|
Sign up to set email alerts
|

Does Intracranial Venous Thrombosis Cause Subdural Hemorrhage in the Pediatric Population?

Abstract: SUMMARY: Unexplained SDH in infants and children is an accepted marker for AHT. It has been proposed that IVT may be the initiating event leading to the development of acute SDH, mimicking the appearance of traumatic SDH. Our study aims to investigate if nontraumatic IVT causes SDH in the pediatric population. We retrospectively identified 36 patients with IVT and reviewed neuroimaging studies for the concurrent presence of SDH. In our 36 patients with IVT, no associated SDH was observed. Even with extensive I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Clinical examples of welldocumented subdural hematoma in infants resulting from venous sinus thrombus (in the absence of trauma) have not been reported after the post-natal period. In fact, a recent study specifically examined imaging studies on infants who presented with primary venous sinus thrombosis and found that none of the infants who were not newborns had subdural hematoma [30].…”
Section: Theory: Unexplained Subdural Hematomas In Infants Can Be Thementioning
confidence: 98%
“…Clinical examples of welldocumented subdural hematoma in infants resulting from venous sinus thrombus (in the absence of trauma) have not been reported after the post-natal period. In fact, a recent study specifically examined imaging studies on infants who presented with primary venous sinus thrombosis and found that none of the infants who were not newborns had subdural hematoma [30].…”
Section: Theory: Unexplained Subdural Hematomas In Infants Can Be Thementioning
confidence: 98%
“…Identification of cortical sinus and venous thrombosis can be a challenge because of the anatomical variations in venous anatomy and limitations of noninvasive neuroimaging techniques such as MR venography and CT venography. However, several previous studies have defined the clinical and neuroimaging findings in children with cortical sinus and venous thrombosis [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A single study evaluating nontraumatic intracranial venous thrombosis detected no subdural hematoma in the study population (n = 36). 139 Additionally, bleeding from intracranial thrombosis has a typical appearance on magnetic resonance imaging, including localized bleeding near the thrombus, typically in an intraparenchymal distribution. This appearance is in contrast to the typical presenting features of deceleration head trauma, including thin-film subdural hemorrhages involving the interhemispheric region and the cerebral convexities.…”
Section: Intracranial Venous Thrombosis Mimicking Abusive Head Traumamentioning
confidence: 99%